"Lectores para la justicia" como proyecto de investigación-acción : aproximaciones filosóficas - Costable, Ornella (2016)
In this paper we propose to think about philosophical and methodological foundations of the research-action in the University. We start with the analysis of the UBACyT Project "Readers for Justice". We argue that the Communitarianism has several points in common with the purpose of the project. We also understand that qualitative methodology is a great support for this kind of program, linking literature, teaching and action within/to the community.